Relationship of PROP (6-n-propylthiouracil) taster status with the body mass index and food preferences of Filipino adults - Alday, Judit Culing; Villarino, Blanca J. (2007., 2007)
ABSTRACT The study aimed to determine the PROP (6-n-propylthiouracil) taster status of Filipino adults and to examine relationship among PROP sensitivity with body mass index (BMI), food preferences, and energy and nutrient intake of the sample population. Self-reported three-day food records and food preference checklists were administered to respondents classified according to their body mass indices (BMI). Increasing concentrations of PROP and NACl solutions were rated in labeled magnitude scale (LMS) and were evaluated to determine the PROP taster status of the selected participants. The Filipino adult population in this study was found to be 12% nontasters, 45% medium tasters, and 43% supertasters. Sweet-tasting foods were most preferred and bitter-tasting foods were least preferred within PROP taster status. On the other hand, medium tasters and supertasters had the highest acceptance for meats, fish and poultry and least acceptance for beverages which were mostly bitter. Decreased preferences for fats and oils, sugars and confectionary, and beverages were highly associated (p<0.05) with responsiveness to PROP. No association between BMI and PROP taster status was found.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Taste -- Threshold; Food preferences